Orienting attention in time: behavioural and neuroanatomical distinction between exogenous and endogenous shifts. - Coull, J; Frith, C; Büchel, C; Nobre, A (2000)
Temporal orienting of attention is the ability to focus resources at a particular moment in time in order to optimise behaviour, and is associated with activation of left parietal and premotor cortex [Coull, J. T., Nobre, A. C. Where and when to pay attention: the neural systems for directing attention to spatial locations and to time intervals as revealed by both PET and fMRI. Journal of Neuroscience, 1998, 18, 7426-7435]. In the present experiment, we explored the behavioural and anatomical correlates of temporal orienting to foveal visual stimuli, in order to eliminate any spatial attention confounds. We implemented a two-way factorial design in an event-related fMRI study to examine the factors of trial validity (predictability of target by cue), length of delay (cue-target interval), and their interaction. There were two distinct types of invalid trial: those where attention was automatically drawn to a premature target and those where attention was voluntarily shifted to a delayed time-point. Reaction times for valid trials were shorter than those for invalid trials, demonstrating appropriate allocation of attention to temporal cues. All trial-types activated a shared system, including frontoparietal areas bilaterally, showing that this network is consistently associated with attentional orienting and is not specific to spatial tasks. Distinct brain areas were sensitive to cue-target delays and to trial validity. Long cue-target intervals activated areas involved in motor preparation: supplementary motor cortex, basal ganglia and thalamus. Invalid trials, where temporal expectancies were breached, showed enhanced activation of left parietal and frontal areas, and engagement of orbitofrontal cortex bilaterally. Finally, trial validity interacted with length of delay. Appearance of targets prematurely selectively activated visual extrastriate cortex; while postponement of target appearance selectively activated right prefrontal cortex. These findings suggest that distinct brain areas are involved in redirecting attention based upon sensory events (bottom-up, exogenous shifts) and based upon cognitive expectations (top-down, endogenous shifts).